Maternal supplementation with Limosilactobacillus reuteri FN041 for preventing infants with atopic dermatitis: study protocol for a randomized controlled trial - Yu, Renqiang; Ma, Yizhe; Luo, Zichen; Qi, Ce; Xie, Anni; Jiang, Yifan; Zhu, Baoli; Sun, Jin (Frontiers in Microbiology, 2023)
Background: Atopic dermatitis (AD) has increased rapidly with rapid urbanization; however, the treatment options for AD are lacking because the commonly used therapies can only alleviate symptoms. Limosilactobacillus reuteri FN041 is a specific strain isolated from human breast milk, and its protective potential against AD has been confirmed. This study aimed to assess the efficacy of maternal consumption of L. reuteri FN041 during late pregnancy and lactation in preventing infantile AD.Methods: First, a randomized, double-blind, placebo-controlled intervention study was conducted on 340 pregnant females with babies at high risk for AD. These subjects were randomly divided into four groups of different doses of L. reuteri 2 FN041 (1 × 10 9 , 5 × 10 9 , and 1 × 10 10 CFU/d) along with a placebo. The safety and efficacy of maternal use of L. reuteri FN041 for preventing infantile AD were analyzed, and the most efficient dosage of L. reuteri FN041 was determined.Subsequently, a multicenter cohort study of 500 pregnant females with babies at high risk for AD was conducted to promote the maternal application of L. reuteri FN041. These subjects were administered L. reuteri FN041 at the optimal dose determined during the first stage of late pregnancy and lactation, and their babies were analyzed for AD development. Recruitment was initiated in October 2022.Discussion: The primary outcome was the cumulative incidence of AD at 24 months after maternal consumption of L. reuteri FN041 during late pregnancy and lactation, whereas the secondary outcome was the efficiency of L. reuteri FN041 transfer from the mother's gut to breast milk and then the infant's gut after oral supplementation.This study demonstrated the efficacy of edible probiotics isolated from breast milk in preventing or treating AD in infants. Accordingly, we provide population-based advice for administering specific probiotics for the primary prevention of AD in pregnant females. Understanding the underlying mechanisms of probiotic strains derived from breast milk can promote their application in preventing infant diseases associated with intestinal microbiota imbalance and immune disorders.